Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376368
|View full text |Cite
|
Sign up to set email alerts
|

PV-Tiles: Towards Closely-Coupled Photovoltaic and Digital Materials for Useful, Beautiful and Sustainable Interactive Surfaces

Abstract: The interactive, digital future with its seductive vision of Internet-of-Things connected sensors, actuators and displays comes at a high cost in terms of both energy demands and the clutter it brings to the physical world. But what if such devices were made of materials that enabled them to self-power their interactive features? And, what if those materials were directly used to build aesthetically pleasing environments and objects that met practical physical needs as well as digital ones? In this paper we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…With his help, we surveyed the built environments in Dharavi and found that tiles are not only a pervasive and aesthetically decorated building material, but also one that is manufactured locally by potters who have been working in Dharavi for over a century [14]. This suggested that the PV-Tiles concept, as developed by Meena et al [21], would be a fruitful starting place to explore and co-design self-powered computational materials that could be embedded into Dharavi's built environment and potentially even manufactured nearby. The PV-Tiles concept closely couples the energy harvesting material with an interactive display and sensors into a tile module so that self-powering interfaces can be fully integrated with surfaces as diverse as kitchen walls, foors and tabletops.…”
Section: Re-imagining Building Materials In Slum Settingsmentioning
confidence: 99%
See 4 more Smart Citations
“…With his help, we surveyed the built environments in Dharavi and found that tiles are not only a pervasive and aesthetically decorated building material, but also one that is manufactured locally by potters who have been working in Dharavi for over a century [14]. This suggested that the PV-Tiles concept, as developed by Meena et al [21], would be a fruitful starting place to explore and co-design self-powered computational materials that could be embedded into Dharavi's built environment and potentially even manufactured nearby. The PV-Tiles concept closely couples the energy harvesting material with an interactive display and sensors into a tile module so that self-powering interfaces can be fully integrated with surfaces as diverse as kitchen walls, foors and tabletops.…”
Section: Re-imagining Building Materials In Slum Settingsmentioning
confidence: 99%
“…While the liaison recruited participants, spoke with potters and found space in a community centre for us to host a design workshop, the team of researchers developed probes-strategically incomplete prototypes-to surface specifc material constraints or material properties of self-powered interfaces and interactions as suggested in [21]. Our co-design workshops with residents of Dharavi, therefore, became a dialogue of people, place, and self-powered digital materials [30].…”
Section: Re-imagining Building Materials In Slum Settingsmentioning
confidence: 99%
See 3 more Smart Citations